Biotechnological Interventions to Combat against Charcoal Rot and Rhizoctonia Root Rot Diseases of Soybean [Glycine max (L.) Merrill] - Upadhyay, Shikha; Singh, A. K.; Tripathi, M. K.; Tiwari, Sushma; Tripathi, Niraj (Current Topics in Agricultural Sciences Vol. 6, 2022)
Soybean is a prime legume in a world's oilseed cultivation set-up. Yield of soybean hampered by several biotic and abiotic stresses including drought. Among different biotic stresses, Charcoal rot and Rhizoctonia root rot are the leading diseases for a huge damage in soybean production and still there is no prominent work has been done effectually to address these problems. Biotic stresses can be controlled by using an integrated management approach either by cultural practices including crop rotation, tillage, irrigation, or chemical control like seed treatments could be employed to diminish damage instigated by fungal pathogen in soybeans. The current study was conducted with the objective to characterize soybean genotypes for yield and its accrediting characters along with validation of gene-based SSR molecular markers against charcoal rot and Rhizoctonia root rots diseases. On the basis of different traits, genotypes viz., JS335, JS20-69, JS97-52, KDS980 and KDS992 were found to be the most divergent and promising genotypes and may be employed as parents in future hybridization programme to breed tolerance/ resistance against Rhizoctonia root rot and charcoal rot by means of conventional and/or molecular breeding approaches.